A diagnosis of the basic requirements for mainstreaming a gender perspective in the bachelor´s degree in Journalism at the Universidad Austral de Chile (Valdivia) - Contreras Gómez, Sofía; Sarmiento, Consuelo; Cárcamo-Ulloa, Luis; Huerta Andrade, Norma (Comunicación y Género [Communication and Gender], 2020)
Diagnosis of the conditions to incorporate gender perspective in the training of journalists graduated from the Universidad Austral de Chile. Aspects of its study plan were analyzed, such as gender parity in the bibliographical references of the subjects, the pedagogical action of teachers and the learning process by students. It was acknowledged that there is a willingness for training in gender issues and social equity, also that there is a positive identification of cultural patterns that limit progress in gender equity issues and encouragement to include a transversal approach of the gender perspective in the curriculum. This was based on theories about the social construction of gender roles, research on journalistic practices that reinforce gender stereotypes and how these affect public opinion and the academic formation of journalists.
Keywords: journalism; education; gender; stereotypes; communication